Andrologické a neandrologické indikace intracytoplazmatické injekce spermie (ICSI) - Mardešić, Tonko; Zetová, L; Hüttelová, Renata; Miková, M; Müller, P; Vobořil, J; Ulčová-Gallová, Zdenka; Hulvert, J (Česká gynekologie, 1997)
Intracytoplasmic sperm infection (ICSI) is a very valuable method which implies a qualitative contribution to assisted reproduction and andrologically conditioned sterility, in particular. However, as one of the methods of cellular surgery it has its defined indications which must be respected.
Keywords: Spermatozoa; injekce; Humans; Cytoplasm; Infertility, Male; lidé; Female; mužská infertilita; Pregnancy; Injections; těhotenství; Infertility, Female; fertilizace in vitro; spermie; Fertilization in Vitro; cytoplazma; ženské pohlaví; ženská infertilita